Perancangan Sistem Informasi Impor & Ekspor (Sieb) Berbasis Web pada PT.Windu Eka - Zulkarnain, Novan (ComTech: Computer, Mathematics and Engineering Applications, 2014)
Exports and imports are driving the nation's economy and state revenue sources. Customs as a state agency is assigned to manage the country's income. Customs and its staff are still experiencing difficulties in reporting receipt of export and import of plant or company. One of the policy is issued, each factory or company shall make the information system to determine information about the export of finished goods and raw material imports. The problem is the lack of standardization in the information that must be made by the manufacturer or company. The problem is the lack of standardization in the information that must be made by the manufacturer or company. This study makes the design of information systems based on web-based exports and imports that can be used by all factories or companies in Indonesia, particularly in PT.Windu Eka. The design method used is the SDLC (System Development Life Cycle) Analysis, Design and Testing Prototype. This information system consists of web-based software with PHP programming and MySQL database that aims to provide information online, so the reports more accessible and faster made to be reported to Customs.